Методи аналізу статичної стійкості виконавчих компонентів комп’ютерних систем - Чабан, Зоряна Іванівна (Національний університет "Львівська політехніка", 2014)
Дисертація присвячена розробці методів аналізу статичної стійкості усталених періодичних станів електромеханічних виконавчих компонентів комп’ютерних систем управління із зосередженими й розподіленими параметрами. Аналіз здійснюється у часовій області на підставі загальної теорії нелінійних диференціальних рівнянь зі звичайними й частинними похідними. Водночас розв’язується задача Коші і двоточкова крайова задача для диференціальних рівнянь. Стійкість періодичного розв’язку визначається за мультиплікаторами Флоке фундаментальної матриці. Задача розв’язується на підставі поєднання методів теорії електромагнітних кіл, теорії квазістаціонарного електромагнетного поля, динаміки механічного руху. Таке поєднання дає можливість найпростіше й найповніше врахувати складний фізичний процес і записати при тому диференціальні рівняння системи в нормальній формі Коші, спростивши тим самим комп’ютерну реалізацію дискретної моделі по максимуму. У загальному алгоритмі задіяні відомі математичні моделі і розроблено нові. Приводяться результати комп’ютерної симуляції. Дисертаційна робота складається зі вступу, чотирьох розділів, висновків, листа використаних джерел. Диссертация посвящена разработке метода анализа статической устойчивости периодических состояний электромеханических исполнительных устройств с сосредоточенными и распределенными параметрами, как составляющих компьютерных систем управления. Анализ осуществляется в часовой области на основании общей теории нелинейных дифференциальных уравнений с обыкновенными и частными производными. Одновременно решается задача Коши и двухточечная краевая задача для дифференциальных уравнений. Устойчивость периодического решения определяется на основании мультипликаторов Флоке фундаментальной матрицы. Задача решается на основании объединения методов теории электромагнитных цепей, теории квазистационарного электромагнитного поля, динамики механического движения. Такое обобщение позволяет наиболее просто и наиболее полно учесть сложный физический процесс и записать при этом дифференциальные уравнения системы в нормальной форме Коши, упростив тем самым реализацию дискретной модели на ЭВМ по максимуму. В общем алгоритме задействуются известные математические модели и разработаны новые. Приводятся результаты расчетов на ЭВМ. Диссертационная работа состоит из введения, четырех глав, выводов, списка использованных литературных источников. The dissertation is devoted to building of method of analysis of static stability of periodical steady-state processes of electromechanical executing devices with concentrated and distributed parameters as subsystems of computer systems of control. Analysis is realized in time area on base of general theory of non-linear differential equations with ordinary and partial derivatives. There is solved Cauchy problem and two point boundary value problem for differential equations. The stability of periodical solution is determined on base of Flock’s multiplicators of fundamental matrix. The problem is solved on base of combination of electromagnetic field theory, electromagnetic circuit’s theory and dynamics of motion. Such combination gives the possibility the simplest and the best to take into consideration complicated physical process and to write down differential equations of system in Cauchy’s form, thanks to simplify computation of discrete model much as possible. In common algorithm is used known mathematical models and created new. The results of computation are given. The work consists: entry, four chapters, conclusions and list of used sources. In entry is shown the actuality of the problems, scientific novelty and practical importance of received results. In the first chapter is made critical analysis of used sources and is shown the expediency to use for static stability solution of method of model of sensitivity to initial condition of differential equations of state. The second chapter consists: theoretical main principles of dissertation which are built on non-linear differential equations general theory, theory of electromagnetic circuits and electromagnetic field. Here is solved Cauchy problem and two point boundary value problem for differential equations of electromechanical state. Here are shown as previous results take on solution of asymptotic stability too. In the third chapter are built mathematical models of analysis of steady-state of electromechanical devices with concentrated electrical and mechanical parameters and determining of asymptotic stability of them. Here are computed stab¬le and unstable steady-state processes. In the fourth chapter the theoretical results of previous two chapters are generalized on systems with distributed electrical parameters. The appropriate mathematical models are built on conception of combination of theories of electromagnetic circuits and electromagnetic field. Here are computed stable and unstable steady-state processes also.
Методы анализа статической устойчивости исполнительных элементов компьютерных систем
The methods of analysis of static stability of actuating components of computer systems
Keywords: компоненти комп’ютерних систем; статична стійкість; математичні моделі; нелінійні електромеханічні системи із зосередженими й розподіленими параметрами; електромагнетні кола; електромагнетне поле; задача Коші й двоточкова крайова задача для диференціальних рівнянь; составляющие компьютерных систем; статическая устойчивость; математические модели; нелинейные электромеханические системы с сосредоточенными и распределенными параметрами; электромагнитные цепи; электромагнитное поле; Задача Коши и двухточечная краевая задача для дифференциальных уравнений; computer systems components; static stability; non-linear electromechanical systems with concentrated and distributed parameters; electromagnetic circuits; electromagnetic field; Cauchy problem and two point boundary value problem for differential equations